5G-SMART DIABETES: TOWARD PERSONALIZED DIABETES DIAGNOSIS WITH HEALTHCARE BIG DATA CLOUDS - M. Venkat Sathya Sravani, P. Poojitha, Pranavi Joshi, B. Prathyusha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This project uses today’s 5G technology to monitor condition of diabetic patients with low cost. Now-a-days many peoples are suffering with diabetic disease due to work stress or unhealthy lifestyles and peoples will not know about the current health condition till symptoms appear or diagnosis through medical check-up and the condition of disease will be severe by that time and there is no possible way to get that intimation prior. Diabetes will be of two type’s diabetes-1 and diabetes-2. Diabetes-2 require hospitalization and in diabetes-1 condition we can monitor patient and alert him or doctors about his current condition